Motion control of an autonomous vehicle with loss of wheel-ground contact avoidance using dynamic model based predictive control. - Kim, Bumsoo. (University of Ottawa (Canada), 2001)
Autonomous motion of vehicles requires an operational space control approach which is able to generate and correct the trajectory of the vehicle in order to avoid collisions with unexpected obstacles and takes into account the contact forces between the wheels and the ground such that the slippage and tip-over of the vehicle can be avoided. A dynamic model of the autonomous vehicle is required for such a control approach in order to verify continuously wheel-terrain contact stability. For achieving autonomy, the dynamics based control approach is formulated for a three-wheeled vehicle with front wheel driving and steering. Exact input-output linearization of the vehicle dynamics facilitates the design of the operational space control and permits the enhancement of the autonomy of the vehicle. However, the sufficient smoothness condition for applying feedback linearization has to be continuously observed and this requires the avoidance of actuators torque saturation, wheel-ground longitudinal and lateral slippage and tip-over of the vehicle for motion on horizontal plane as well as inclined surfaces. In this thesis, first is presented a complete three dimensional kinematic and dynamic model of a three-wheeled autonomous vehicle built in our laboratory. Newtonian dynamics was used for developing the dynamic model of the autonomous vehicle. It continues with the path planning algorithm using the Timoshenko's 4th order differential slender beam equation and the analysis of the two part control scheme. The control scheme contains an external loop for a linear controller, a path planner in operational space, and an inner loop exact input-output linearization controller in curvilinear space (s-delta). A dynamic model based predictive control is proposed for avoidance of the violation of the smoothness condition for exact linearization, while at the same time conserving path planning results by modifying the input commands.
Keywords: Engineering, Mechanical.